Rise and fall: Effects of tone and intonation on spoken word recognition in early childhood. (March 2016) - Singh, Leher; Chee, Melissa
Abstract: A crucial component of word learning is the ability to recognize words in spite of the varying forms they assume. This may be particularly challenging in tone languages as learners have to develop tone representations in the face of intonational variation in order to accurately recognize words. The effects of intonational variation on word recognition of tone-marked words in Mandarin Chinese were investigated in toddlers and preschoolers using a cross-sectional design. Participants were presented with known words where intonation (question/statement) and tone (rising/falling) were independently manipulated. Results demonstrated that word recognition in toddlers was heavily influenced by changes in the pitch contour of a tone due to intonational variation. In contrast, preschool were able to recognize tone-marked words regardless of simultaneous intonational variation, demonstrating a comparatively robust representation of lexical tone. Results chart an evolution in integrating pitch cues to tone and intonation over the first few years of life. Highlights: We examined word recognition in toddlers and preschoolers. Target words varied in tone and intonation. Toddlers only recognized words when tone and intonation converged. Preschoolers recognized words regardless of tone and intonation cues. Generalizing over intonation in tone-marked words is observed at 4–5 years of age.